Caracterización de los parásitos gastrointestinales en las ganaderías de la parroquia Calceta del cantón Bolívar - Lucas Basurto, Manuel Patricio (2024)
The research was conducted in Calceta parish, Bolívar canton, Manabí province, with the aim of identifying the presence and typology of gastrointestinal parasites in cattle. The coproparasitic analysis technique using phenol solution was employed, sampling 339 cattle of different ages and sexes. The fecal samples were analyzed in the Chemistry laboratory of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López and processed using Microsoft Excel 2016. The results showed a gastrointestinal parasitism prevalence of 79%, with a higher incidence of Trichostrongylus sp. (43%), Trichuris sp. (24%) and Moniezia expansa (21%). Although no significant association was found between the age of the cattle and the presence of parasites (p > 0.05), a moderate relationship was observed with the species, with Bos Taurus being more susceptible than Bos Indicus (p = 0.0231). Additionally, biannual deworming was identified as the most common practice, although its effectiveness may be compromised by the improper use of dewormers, contributing to parasite resistance. These results highlight the importance of establishing adequate sanitary protocols to improve animal health and prevent productive losses in the cattle farms of Calceta parish.